2021
DOI: 10.3389/fendo.2021.790160
|View full text |Cite
|
Sign up to set email alerts
|

Growth Hormone Cotreatment for Low-Prognosis Patients According to the POSEIDON Criteria

Abstract: BackgroundPoor ovarian response (POR) remains one of the most challenging conditions in assisted reproduction technology. Previous studies seemed to indicate that growth hormone (GH) was a potential solution for the dilemma of POR; however, the role GH played on the low-prognosis patients diagnosed and stratified by the POSEIDON criteria remains indistinct.MethodsThis retrospective study was performed among women with POR according to the POSEIDON criteria who failed a previous in vitro fertilization (IVF)/int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 26 publications
(38 reference statements)
1
5
0
Order By: Relevance
“…Consistent with the results reported by Liu et al. ( 27 ), we presented a tolerable live birth rate in GH+ cycle in similar to that reported in aged women in their study (POSEIDON group 2: 28.33%; group 4: 24.07%). Besides, a cumulative live birth rate per cycle of 33.33% was achieved in the GH+ cycle when comparable number of embryos transferred and much more transferrable embryos remained, which may also suggest the underlying effect of GH on ameliorating embryo quality.…”
Section: Discussionsupporting
confidence: 93%
“…Consistent with the results reported by Liu et al. ( 27 ), we presented a tolerable live birth rate in GH+ cycle in similar to that reported in aged women in their study (POSEIDON group 2: 28.33%; group 4: 24.07%). Besides, a cumulative live birth rate per cycle of 33.33% was achieved in the GH+ cycle when comparable number of embryos transferred and much more transferrable embryos remained, which may also suggest the underlying effect of GH on ameliorating embryo quality.…”
Section: Discussionsupporting
confidence: 93%
“…For example, several randomized controlled trials did not detect any definitive benefits of GH administration on live birth rates in poor ovarian responders (29, 30). However, other studies have reported improvements in pregnancy, implantation, and live birth rates following GH supplementation (8,(10)(11)(12)31). This discrepancy can be attributed to differences in patient groups.…”
Section: Discussionmentioning
confidence: 97%
“…The recent meta-analysis by Cozzolino et al 49 showed that supplementation of GH in POR patients increased the clinical pregnancy rate, but did not affect the ongoing pregnancy rate and live birth rate. Some single studies have also drawn inconsistent conclusions 35,46,50 . In our NMA, no GH supplementation protocol has been proven effective in improving the clinical pregnancy rate and live birth rate of POR patients according to the overall pooled results.…”
Section: Discussionmentioning
confidence: 99%